IL (Interleukin)-15 Bridges Astrocyte-Microglia Crosstalk and Exacerbates Brain Injury Following Intracerebral Hemorrhage - Shi, Samuel X.; Li, Yu-Jing; Shi, Kaibin; Wood, Kristofer; Ducruet, Andrew F.; Liu, Qiang (Stroke (1970), 2020)
BACKGROUND AND PURPOSE—Microglia are among the first cells to respond to intracerebral hemorrhage (ICH), but the mechanisms that underlie their activity following ICH remain unclear. IL (interleukin)-15 is a proinflammatory cytokine that orchestrates homeostasis and the intensity of the immune response following central nervous system inflammatory events. The goal of this study was to investigate the role of IL-15 in ICH injury. METHODS—Using brain slices of patients with ICH, we determined the presence and cellular source of IL-15. A transgenic mouse line with targeted expression of IL-15 in astrocytes was generated to determine the role of astrocytic IL-15 in ICH. The expression of IL-15 was controlled by a glial fibrillary acidic protein promoter (GFAP-IL-15). ICH was induced by intraparenchymal injection of collagenase or autologous blood. RESULTS—In patients with ICH and wild-type mice subjected to experimental ICH, we found a significant upregulation of IL-15 in astrocytes. In GFAP-IL-15 mice, we found that astrocyte-targeted expression of IL-15 exacerbated brain edema and neurological deficits following ICH. This aggravated ICH injury in GFAP-IL-15 mice is accompanied by increased microglial accumulation in close proximity to astrocytes in perihematomal tissues. Additionally, microglial expression of CD86, IL-1β, and TNF-α is markedly increased in GFAP-IL-15 mice following ICH. Furthermore, depletion of microglia using a colony stimulating factor 1 receptor inhibitor diminishes the exacerbation of ICH injury in GFAP-IL-15 mice. CONCLUSIONS—Our findings identify IL-15 as a mediator of the crosstalk between astrocytes and microglia that exacerbates brain injury following ICH.